Tackling adult innumeracy - Tom Nesbit (Adult Education Research Conference, 1994)
Twenty-five years ago, the traditional educational response to adult illiteracy was simply framed in two key questions: Was whole language or phonics the correct approach? Which textbooks were most useful? There was little attempt to place illiteracy in any historical cultural, or social context, or to greatly consider the needs and aims of adult learners. Today such notions seem hopelessly reductive, and yet educators largely perpetuate a similarly inadequate response to an equally grave problem--adult innumeracy. The urgency of addressing innumeracy demands more creative approaches to mathematics education for adults.